2017
DOI: 10.1016/j.eats.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

The “Floating Labrum”: Bankart Lesion Repair With Anterior Capsular Extension Using 2 Anterior Working Portals

Abstract: Surgical repair of a Bankart lesion requires thorough recognition of the capsulolabral attachment and adequate visualization for suture anchor repair. The glenoid labrum usually detaches from its capsule and bony attachment anteriorly and inferiorly; however, the labral and capsule detachment can sometimes extend beyond this zone of injury. Identification and repair may require additional viewing and working portals to allow for ease of suture passage and anchor placement. This technique guide describes a case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The time from the index OLP to screw removal was 29 6 37 months (median, 16; range, 6-138). Age at screw removal was 25 6 6 years (median, 25; range [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. All patients had surgery under general anesthesia with an interscalene block and in the beach-chair position performed by 1 experienced surgeon (A.G.).…”
Section: Arthroscopic Assessment and Screw Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…The time from the index OLP to screw removal was 29 6 37 months (median, 16; range, 6-138). Age at screw removal was 25 6 6 years (median, 25; range [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. All patients had surgery under general anesthesia with an interscalene block and in the beach-chair position performed by 1 experienced surgeon (A.G.).…”
Section: Arthroscopic Assessment and Screw Removalmentioning
confidence: 99%
“…Anterior shoulder instability is a common indication for surgery, especially in young athletes. 6,29,31 Its common surgical treatments include Bankart (labral) repairs, which involve sewing the joint capsule and detached labrum to the glenoid, 25,32 and Latarjet (bone block) procedures, which require transferring the coracoid process, with attached soft tissue, to the anteroinferior border of the glenoid through a split in the subscapularis muscle. 12,13,40 The Latarjet procedure enables fast recovery 2 and return to sports, 22 has a low recurrence of instability (\7%), 9,19 and includes favorable long-term outcomes, 14,20,41 despite some complications, such as pain at the tip of the screw, 11,28,33 bone-block lyses, malposition, nonunion, 11,23,33,35 and neurological dysfunction.…”
mentioning
confidence: 99%
“…Anterior shoulder instability often requires surgical treatment, particularly in young athletes that wish to resume sports [5, 29, 31]. The most common surgical procedures involve arthroscopic labral or capsular repair [27, 32], and open or arthroscopic bone‐block procedures [9, 21], which transfer the coracoid process through a subscapularis split to the anteroinferior margin of the glenoid [12, 40].…”
Section: Introductionmentioning
confidence: 99%
“…3 Some patients show a recurrent dislocation rate of up to 90 percent and are commonly treated with arthroscopic labrum repair, capsular repair, and open bone-block techniques. 4,5,6,7 The rates of recurrent instability are documented up to 10-22.5 percent in a few case series and are mostly found in younger patients and patients with substantial bone loss. 8,9,10,11 It has been observed that the arthroscopic recurrence rate is 67 per cent in case of bone loss, whereas Bankart repair has reported a recurrence rate of 4 per cent without a bone loss Michel Latarjet, in 1954, described a blocking technique of later-jet and preferred it for patients having recurrent anterior dislocation of the shoulder with a bone loss.…”
Section: Introductionmentioning
confidence: 99%